Digital Business Ecosystems: solving pain points for smallholder farmers and identifying opportunities for service providers - Davidson, Nontokozo (Graduate School of Business (GSB), 2024)
Smallholder farmers have difficulty accessing markets and market information necessary for them to be highly productive and profitable. Digital technologies and digital business ecosystems (platforms) have been solving longstanding problems across different sectors including commercial agriculture, however, such developments have not received widespread adoption across smallholder farming. The objective of this study is to explore how the benefits of digital business ecosystems can solve critical challenges for smallholder farmers in sub-Saharan Africa, focusing on Eswatini. The study also looks at factors required to scale up the use of digital platforms and explores untapped business opportunities for digital business ecosystems for service providers and smallholder farmers. The study employed semi-structured interviews to collect data from eight smallholder farmers and seven service providers. They were purposively selected participants in Eswatini, selected for their respective perspectives and experiences on digital business ecosystems in the smallholder value chain. The data was analysed using qualitative thematic analysis. Analysis shows that the benefits, and improvements from the use of digital platforms/technologies include market linkages, growth in sales and profits, ease of doing business, and access to market information. Collaboration among value chain actors and pooled customer numbers the study reveals, can also be used to leverage digital business ecosystems to boost smallholder farmers' productivity and economic activity. In addition, the study has identified quality assurance, drone technology, and geolocation services, as well as rural agriculture, as opportunities for the smallholder sector under digital technologies and platforms. Low investment levels, insufficient digital literacy, expensive internet access, and a lack of consistent markets, on the other hand, are barriers to the successful adoption and scaling up of digital ecosystems. The findings highlight the need for significant investment to improve the acceptance and widespread use of digital business ecosystems in smallholder farming